2017
DOI: 10.18632/oncotarget.16539
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oncogenic mutations in resected bronchial margins by next-generation sequencing indicates early relapse in stage IA lung adenocarcinoma patients

Abstract: Stage I non-small cell lung cancer (NSCLC) patients experience a relatively high rate of recurrence, ranging from about 30-35%. We hypothesized that this elevated risk of recurrence is due to the presence of tumor cells at bronchial margins which was undetected by conventional light microscopy. Patients with clinical stage IA (T1N0M0) NSCLC were enrolled in this study, which included 8 early-relapse(ER) and 6 no-relapse(NR) patients. Primary tumor, bronchial margin, and normal lung tissues were collected and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 18 Another study by Lv et al found that oncogenic mutations were identified in 87.5% bronchial margins of early relapse patients, suggesting that genetic alterations in the margins may be risk factors of recurrence in lung cancer patients at early stages. 19 In our study, we found that oncogene mutations occurred in 94.3% and 13.6% of tumor cases and marginal tissues using NGS, respectively. Most of the gene mutations detected were cancer drivers.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“… 18 Another study by Lv et al found that oncogenic mutations were identified in 87.5% bronchial margins of early relapse patients, suggesting that genetic alterations in the margins may be risk factors of recurrence in lung cancer patients at early stages. 19 In our study, we found that oncogene mutations occurred in 94.3% and 13.6% of tumor cases and marginal tissues using NGS, respectively. Most of the gene mutations detected were cancer drivers.…”
Section: Discussionmentioning
confidence: 53%
“…[15][16][17] Only a few studies have explored the molecular status of histologically normal-appearing surgical margins. [18][19][20] Masasyesva et al analyzed the molecular margins of sublobar resections of lung cancer and identified that K-RAS mutation at codon 12 was associated with local recurrence of NSCLC. 18 Another study by Lv et al found that oncogenic mutations were identified in 87.5% bronchial margins of early relapse patients, suggesting that genetic alterations in the margins may be risk factors of recurrence in lung cancer patients at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] found that nearly 53% of the pancreatic cancer patients had detectable KRAS mutations in their H&E‐negative surgical margins samples, and these pancreatic cancer patients who were positive for surgical margins by the PCR‐based approach had a worse prognosis. Several gene mutations and DNA promoter hypermethylation changes were also successfully found in the surgical margins of NSCLC [ 48 , 49 ]. However, these studies had limited cohort size, utilized single gene sequencing data, or mainly focused on stage I‐II patients.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that the postoperative lung metastasis rate and the poor prognosis are high when the DBRM is large. This may be caused by the following reasons: rstly, when the DBRM is large, the margin is also larger, and the possibility of cancer cell survival will increase, although the later pathological results showed negative, but ordinary optical microscopes could not completely diagnose the remaining cancer cells (17); when the margin is large, the surrounding alveolar tissue is more (18), the adjacent alveolar tissue is destroyed more, and the lung tissue containing tumor cells is exposed the area and space are relatively large, so it is easier for tumor cells to spread through the alveolar space to metastasize (19,20); at the same time, intraoperative operations may cause tumors to spread through the alveolar space or increase exfoliated cells, which will increase the postoperative lung metastasis rate; secondly, the analysis results showed that older patients (≥ 65 years) with central lung cancer are also independent risk factors for postoperative lung metastasis (21), this may be due to the declining of lung function in patients with older age or anatomical factors related, which need to explore furtherly.…”
Section: Discussionmentioning
confidence: 99%